Effectiveness of Using Flip PDF Professional E-Book for Learning Sepak Takraw - Rizki Gustaman; Silvi Aryanti; Herri Yusfi; Samsul Azhar (Universitas Negeri Semarang, 2024)
This study discusses the effectiveness of the use of e-books based on the flip pdf professional sepak takraw application for students of Palembang 6 Senior High School. This study aims to determine the effectiveness of using e-book media based on the flip pdf professional application for sepak takraw learning at Palembang Senior High School. The research method used in this research is Classroom Action Research using two cycles. The subjects in this study consisted of 36 students in class XI Senior High School. Data collection techniques used by conducting tests and observations carried out with several stages, namely: planning, implementation stage, observation stage, and reflection stage. The results of the research obtained in the pre-cycle with obtained classical completeness of 40.5% and obtained the average value of students of 57.6%, in pre-cycle I obtained the results of classical completeness of 56.8% with an average value of 62.8% and obtained results from pre-cycle II classical completeness of students of 86.4% with an average value obtained of 80%. From the results of the data obtained, it can be concluded that the application of the use of e-books based on the professional sepak takraw flip pdf application can be said to be effectively used in learning at Senior High School, South Sumatra.